Efficacy of Fluoride Varnish and Casein Phosphopeptide-Amorphous Calcium Phosphate for Remineralization of Primary Teeth: A Randomized Clinical Trial - Memarpour, Mahtab; Fakhraei, Ebrahim; Dadaein, Shorangize; Vossoughi, Mehrdad (Medical principles and practice, 2015)
Objective: We aimed to evaluate the efficacy of oral hygiene instruction, fluoride varnish and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) for remineralizing white spot lesions (WSL), and the effect of these on the dmft index in primary teeth. Subjects and Methods: In this 1-year, randomized clinical trial, 140 children aged 12-36 months with WSL in the anterior maxillary teeth were selected and randomly divided into 4 groups of 35 children each. Group 1 (control) received no preventive intervention. In group 2, there was oral hygiene and dietary counseling. In group 3, there was oral hygiene and the application of fluoride varnish at 4, 8 and 12 months after baseline. In group 4, there was oral hygiene and tooth mousse was applied by the parents twice a day over a 12-month period. At baseline and 4, 8 and 12 months after the intervention, the size of WSL in millimeters and the dmft index were recorded. One hundred and twenty-two children completed the study. Data were analyzed using the repeated-measures ANOVA test. Results: In group 1, the mean percent WSL area and dmft index values had increased significantly at 12 months after baseline (p < 0.001). The interventions led to significant decreases in the size of the WSL; the greatest reduction was in group 4 (63%) followed by group 3 (51%) and group 2 (10%) after 12 months. The smallest increase in the dmft index was in group 4 (0.17), followed by groups 3 (0.3) and 2 (0.42). However, there were no significant differences between the groups (p < 0.001). Conclusions: Oral hygiene along with four fluoride varnish applications or constant CPP-ACP during the 12- month period reduced the size of WSL in the anterior primary teeth and caused a small increase in dmft index values.